2005
DOI: 10.1111/j.0022-1112.2005.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of offspring from intra‐ and interspecific crosses of Carassius auratus gibelio by chromosome and RAPD analysis

Abstract: The ploidy of silver crucian carp Carassius auratus gibelio individuals, originating from nine natural habitats of Hungary, was estimated by erythrocyte nucleus area analysis. On the basis of DNA polymorphism, the genetic homogeneity or heterogeneity and the chromosome number of different offspring derived from the crossing of triploid and diploid populations and of two types of silver crucian carp females with other cyprinid males (Cyprinus carpio, Carassius carassius, Carassius auratus and Barbus conchonius)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 24 publications
2
49
0
2
Order By: Relevance
“…It has been observed widely in many countries of the Eurasian continent (Gui and Zhou, 2010), such as in Britain (Hanfling et al, 2005), Italy (Hanfling et al, 2005), Hungary (Toth et al, 2005), Germany (Hanfling et al, 2005), Croatia (Jakovlic and Gui, 2011), Greece (Liasko et al, 2010), Kazakhstan (Sakai et al, 2009), Russia (Abramenko et al, 2004;Jiang et al, 2013), China (Gao et al, 2012;Jiang et al, 2013;Li and Gui, 2008), and Japan (Takada et al, 2010). Similar to other unisexual polyploid vertebrates, the polyploid gibel carp can reproduce by spermdependent gynogenesis, and many diverse gynogenetic clones have been discriminated by biological traits and molecular markers (Bai et al, 2011;Gui and Zhou, 2010;Guo and Gui, 2008;Yang and Gui, 2004;Zhou et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed widely in many countries of the Eurasian continent (Gui and Zhou, 2010), such as in Britain (Hanfling et al, 2005), Italy (Hanfling et al, 2005), Hungary (Toth et al, 2005), Germany (Hanfling et al, 2005), Croatia (Jakovlic and Gui, 2011), Greece (Liasko et al, 2010), Kazakhstan (Sakai et al, 2009), Russia (Abramenko et al, 2004;Jiang et al, 2013), China (Gao et al, 2012;Jiang et al, 2013;Li and Gui, 2008), and Japan (Takada et al, 2010). Similar to other unisexual polyploid vertebrates, the polyploid gibel carp can reproduce by spermdependent gynogenesis, and many diverse gynogenetic clones have been discriminated by biological traits and molecular markers (Bai et al, 2011;Gui and Zhou, 2010;Guo and Gui, 2008;Yang and Gui, 2004;Zhou et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was recorded only in Japan (Kobayasi, 1971), Russia (Cherfas, 1981), and China (Jiang et al, 1983;Zhou and Gui, 2002). Recently, along with cytogenetic and molecular marker development, it has been extensively observed in many countries of the Eurasian continent, such as in Britain, Italy, Germany (Hänfling et al, 2005), Hungary (Tóth et al, 2005), Greece (Liousia et al, 2008), Czech Republic (Kalous et al, 2007;Veteŝník et al, 2007), Kazakhstan (Sakai et al, 2009), and Croatia (Jakovlić and Gui, 2011). In the past decade, a lot of genetic knowledge including molecular basis of reproduction trait and numerous polymorphic DNA markers has been investigated and characterized from the triploid form (Gui and Zhou, 2010;Gui and Zhu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid twentieth century, CAC has often been introduced into European fisheries by pisciculturists with the primary aim to fill a vacant ecological niche next to Cyprinus carpio L. (Tóth et al 2005), so escapes from fish farms and releases of ornamental goldfish into natural waters are considered to be the primary causes of fast dispersion (Slavík and Bartoš 2004;Hänfling 2007). Until the 1990s, it was believed that the populations in Europe consisted exclusively of gynogenetic polyploid females (Mezhzherin and Lisetskii 2004;Hänfling et al 2005), whereas more recent studies have found a high proportion of diploid males and females (Abramenko et al 2004;Tóth et al 2005).…”
Section: Introductionmentioning
confidence: 99%